(untitled) - Burch, Hobart A (New York)
Includes bibliographical references and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Social policy -- Methodology; Social planning -- Methodology; Chính sách xã hội -- Phương pháp luận; Quy hoạch xã hội -- Phương pháp luận